Floristic structure of some selected plots in olokemeji forest reserve, Ogun state, Nigeria (2021)
Deforestation disrupts forest structure and function with negative impacts on biodiversity and natural regeneration of the forests. In Nigeria, forests are lost through burning, shifting cultivation and logging of trees. These describe the state of degradation in Olokemeji forest reserve. Hence, a need to evaluate the species composition and floristic structure of the woody species in selected plots of the forest reserve. The forest reserve, situated in the lowland rain forest of south-western Nigeria occupies a total land area of 58.88 km2. Six sample plots of 50 m2 each were randomly selected and designated as Frequently Burnt Plot 1, frequently burnt Plot 2, Harvested Plot, Unharvested unburnt Plot, Arable Plot 1 and Arable Plot 2. One hundred and eighty two stands were enumerated, with unharvested unburnt plot having the highest number of trees at 50. The highest percentage cover was recorded at frequently burnt plot 1, frequently burnt plot 2 and Unharvested unburnt plot which ranged from 21-50%. Trees in Unharvested Unburnt Plot had the highest mean diameters at breast height (78.46cm) and mean heights (14.44 m), while the Arable Plots had lowest mean diameters at breast height and mean heights. There is a high level of anthropogenic interference at the forest reserve, and the structure and composition of the tree species enumerated in the study plots reflected some of the nature of impact. Indiscriminate logging of trees as fuelwood should be greatly curtailed and improvised by the neighbouring communities.